1998
DOI: 10.1046/j.1365-313x.1998.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher plants possess two structurally different poly(ADP‐ribose) polymerases

Abstract: SummaryOne of the immediate reactions of the mammalian cell to many environmental stresses is a massive synthesis of poly(ADP-ribose), catalyzed by poly(ADP-ribose) polymerase (PARP). Most of the biological functions attributed to PARP are inferred from experimentation with mammalian cells. In plants, the biology of PARP may be more complicated and diverse than was previously thought. Two poly(ADP-ribose) polymerase homologues were found in plants, the classical Zn-finger-containing polymerase (ZAP) and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
107
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 44 publications
2
107
0
Order By: Relevance
“…S1A). Orthologs of PARP-1 and PARP-2, the DNA-dependent PARPs, AtPARP1 (At4g02390) and AtPARP2 (At2g31320), respectively, have been identified (Lepiniec et al, 1995;Babiychuk et al, 1998). These genes have been implicated in DNA repair (Doucet-Chabeaud et al, 2001;De Block et al, 2005) and have been shown to be associated with chromosomes through their N-terminal zinc fingers (Babiychuk et al, 2001).…”
mentioning
confidence: 99%
“…S1A). Orthologs of PARP-1 and PARP-2, the DNA-dependent PARPs, AtPARP1 (At4g02390) and AtPARP2 (At2g31320), respectively, have been identified (Lepiniec et al, 1995;Babiychuk et al, 1998). These genes have been implicated in DNA repair (Doucet-Chabeaud et al, 2001;De Block et al, 2005) and have been shown to be associated with chromosomes through their N-terminal zinc fingers (Babiychuk et al, 2001).…”
mentioning
confidence: 99%
“…5 Similar to its human homolog, the XRCC1-like polypeptide of Arabidopsis is predicted to contain multiple protein-protein interaction BRCT (BRCA1 C-terminal) modules. Interestingly, similar BRCT modules are also present in the putative DNA polymerase ␤ as well as in a member of one of the two PARP families thus far described in plants (21). No human polynucleotide kinase 3Ј-phosphatase homolog other than AtZDP is encoded in the Arabidopsis genome.…”
Section: Discussionmentioning
confidence: 95%
“…Genes encoding PARP-homologous proteins with a structural organization resembling that of animal PARPs have been described in higher plants (20,21). More recently, the first plant enzyme catalyzing the repair of DNA 3Ј-blocking lesions has been identified in maize (22).…”
mentioning
confidence: 99%
“…Cultured fibroblasts from PARP Ϫ͞Ϫ mice display PARP activity Ϸ25% of wild-type levels, whereas cultured PARP Ϫ͞Ϫ primary embryonic cells display Ϸ3% of wild-type levels (37). Very recently, novel isoforms of PARP have been identified (38,39). The extent to which they contribute to PARP activity in various mammalian tissues has not been established.…”
Section: Discussionmentioning
confidence: 99%